Case report of dystrophic epidermolysis bullosa confirmed by genetic analysis - Serapinas, Danielius; Aukstuoliene, Egle; Sukys, Marius (Medical Studies/Studia Medyczne, 2015)
Dystrophic epidermolysis bullosa is an inherited disease presenting with blistering of the skin in the subdermal layer caused by gene COL7A1 mutations. The authors reviewed a case of this disease determined by two mutations: dominant and recessive. The disease presented with blisters all over the patient’s body, mostly on the neck, back, and inguinal area, as well as on the hands and feet. The symptom that most affected the patient’s quality of life was severe blistering and ulceration in the pharynx, mucous membrane of the mouth, and perianal area. There is no effective treatment today, only procedures to relieve complications like oesophageal obstructions.